SciPhon: a data analysis software for nuclear resonant inelastic X‐ray scattering with applications to Fe, Kr, Sn, Eu and Dy. (21st August 2018) - Dauphas, Nicolas; Hu, Michael Y.; Baker, Erik M.; Hu, Justin; Tissot, Francois L. H.; Alp, E. Ercan; Roskosz, Mathieu; Zhao, Jiyong; Bi, Wenli; Liu, Jin; Lin, Jung-Fu; Nie, Nicole X.; et al.
Abstract : SciPhon is a software for the reduction of nuclear resonant inelastic X‐ray scattering data. Tests and examples of applications to Fe, Kr, Sn, Eu and Dy data are presented. Abstract : The synchrotron radiation technique of nuclear resonant inelastic X‐ray scattering (NRIXS), also known as nuclear resonance vibrational spectroscopy or nuclear inelastic scattering, provides a wealth of information on the vibrational properties of solids. It has found applications in studies of lattice dynamics and elasticity, superconductivity, heme biochemistry, seismology, isotope geochemistry and many other fields. It involves probing the vibrational modes of solids by using the nuclear resonance of Mössbauer isotopes such as 57 Fe, 83 Kr, 119 Sn, 151 Eu and 161 Dy. After data reduction, it provides the partial phonon density of states of the Mössbauer isotope that is investigated, as well as many other derived quantities such as the mean force constant of the chemical bonds and the Debye velocity. The data reduction is, however, not straightforward and involves removal of the elastic peak, normalization and Fourier–Log transformation. Furthermore, some of the quantities derived are highly sensitive to details in the baseline correction. A software package and several novel procedures to streamline and hopefully improve the reduction of the NRIXS data generated at sector 3ID of the Advanced Photon Source have been developed. The graphical user interface software is named SciPhon and runs as a Mathematica package. It is easily portable to other platforms and can be easily adapted for reducing data generated at other beamlines. Several tests and comparisons are presented that demonstrate the usefulness of this software, whose results have already been used in several publications. Here, the SciPhon software is used to reduce Kr, Sn, Eu and Dy NRIXS data, and potential implications for interpreting natural isotopic variations in those systems are discussed.